1l(8-x)=8-x

Simple and best practice solution for 1l(8-x)=8-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1l(8-x)=8-x equation:


Simplifying
1l(8 + -1x) = 8 + -1x
(8 * 1l + -1x * 1l) = 8 + -1x
(8l + -1lx) = 8 + -1x

Solving
8l + -1lx = 8 + -1x

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-8 + 8l + -1lx + x = 8 + -1x + -8 + x

Reorder the terms:
-8 + 8l + -1lx + x = 8 + -8 + -1x + x

Combine like terms: 8 + -8 = 0
-8 + 8l + -1lx + x = 0 + -1x + x
-8 + 8l + -1lx + x = -1x + x

Combine like terms: -1x + x = 0
-8 + 8l + -1lx + x = 0

The solution to this equation could not be determined.

See similar equations:

| 6w+8=48 | | q/3=31/1 | | 74=28+V | | 4j/12=-1 | | 72-w=8w | | y=rx+3 | | 13b=78 | | X-4=-9-4x | | 5n-2-7n=-14 | | 4x-18=3(2x-9) | | 7-2n=-13-6n | | 7.50p+2.50=12.50 | | 8x+3+4(x-5)= | | 5(r-5)-4(r-1)=2(r+4) | | 2M/(22M^2) | | 3x-2(4x-3)=6-(x+8) | | -7y+3=-22 | | y+2*-4=-6 | | 8w=27+5w | | 9x-2b+8b+3x= | | 3(4x+1)-2(2x-7)=73 | | 70-(3Q+70)=70-4Q | | 4x+5x-2=16 | | 4.5+y=y-5.5 | | 16x+17=73 | | X-(-2-x)=-2(-2x-4) | | 6x+5y=1650 | | 8=(y/3=3/4) | | 17u=48+9u | | −1/2s−7 | | (3n-6)-(4n-8)= | | 6.28r=3.14r^2 |

Equations solver categories